Association between inflammatory indices and preoperative deep vein thrombosis in patients undergoing total joint arthroplasty: a retrospective study - Xiaojuan Xiong; Peng Hu; Ting Li; Shuang Yu; Qingxiang Mao (Thrombosis Journal)
Abstract Background To investigate the association between inflammatory indices-systemic immune-inflammation index (SII), monocyte-lymphocyte ratio (MLR), neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and preoperative deep vein thrombosis (DVT) in patients undergoing total joint arthroplasty (TJA). Methods We created the receiver operator characteristic (ROC) curve using the ratios of SII, MLR, NLR, PLR to DVT before TJA, divided the enrolled patients into groups based on the cut-off value, and then analyzed risk factors for DVT before TJA in the multivariate binary logistic regression analysis. Results A total of 2125 patients were enrolled and preoperative DVT occurred in 110 cases (5.18%). Based on the ROC curve, we determined that the cut-off values for SII, MLR, NLR, and PLR were 470*109 /L, 0.306, 2.08, and 127; and the areas under the curve (AUC) were 0.623, 0.601, 0.611, and 0.62. Multivariate binary regression analysis revealed that the risk of preoperative DVT in TJA patients with SII ≥ 470*109/L, MLR ≥ 0.306, PLR ≥ 127, and NLR ≥ 2.08 increased by 2.26 (P < 0.001, 95% confidence interval (CI) [1.52–3.37]), 1.92 (P = 0.002, 95% CI [1.28–2.9]), 2.1 (P < 0.001, 95% CI [1.4–3.16]), and 1.94 (P = 0.002, 95% CI [1.29–2.92]) times, respectively. Age, P < 0.001, odds ratio (OR) = 1.08, 95%CI [1.05–1.10]; corticosteroid use, P = 0.002, OR 3.8, 95% CI [1.94–9.22]). Conclusion We found that higher SII, MLR, NLR, and PLR levels, age, and corticosteroid use were independent risk factors for preoperative DVT in patients undergoing TJA. Clinical trial registration ChiCTR2100054844; Registration Date: 2021.12.28.